Solid waste-slag synergy and full-particle size optimized fluidized solidified soil and preparation method

By using alkali-activated solid waste-based gelling materials and composite thickeners in fluid solidified soil, the resource utilization problems of shield slag and industrial solid waste are solved, and the performance of fluid solidified soil is improved, achieving resource utilization and environmentally friendly solidification effects.

CN118005360BActive Publication Date: 2025-04-04OCEAN UNIV OF CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410165430.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-05
Publication Date
2025-04-04
Estimated Expiration
2044-02-05

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively utilize shield slag and industrial solid waste, resulting in waste of resources and environmental pollution. At the same time, the fluidity, water excretion rate and compressive strength of the fluidized solid soil are difficult to coordinate.

Method used

The alkali-activated solid waste-based gelling material is used as the slag curing agent, and combined with the synergistic effects of composite thickener, water reducing agent, foaming agent and activated magnesium oxide, the preparation of fluid solidified soil with optimized full particle size is carried out to replace the traditional cement curing agent.

Benefits of technology

The resource utilization of shield slag and industrial solid waste has been realized, energy consumption and carbon dioxide emissions have been reduced, the fluidity, compressive strength and stability of fluid solidified soil have been improved, and the problem of poor performance of fluid solidified soil has been solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118005360B_ABST
    Figure CN118005360B_ABST
Patent Text Reader

Abstract

The present invention provides a fluidized solidified soil with solid waste-slag synergy and full-particle size optimization and a preparation method. The fluidized solidified soil is composed of full-particle size optimized solid waste-based cementitious materials (modified graphite tailings, red mud, slag powder, fly ash, steel slag), full-particle size optimized shield slag, mixing water, and admixtures (composite alkali activator, composite thickener, water reducer, defoamer, foaming agent, activated magnesium oxide), so as to realize the resource recycling of shield slag, graphite tailings, red mud, slag powder, fly ash and steel slag. Cement materials are no longer used as soil curing agents, thereby reducing energy consumption and carbon dioxide emissions. And the prepared fluidized solidified soil has the advantages of high density, good fluidity, low water seepage rate and high curing strength. It can be used for backfilling and pouring of various fertilizer troughs, foundation pits, municipal pipelines, mines, shield wall back space and other projects, and can also be applied to roadbeds, building foundations, hydraulic geotechnical, marine geotechnical and other reinforcement fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of civil engineering materials, and in particular to fluidized solidified soil based on coordinated full-particle size optimization of solid waste slag and a preparation method thereof. Background Art

[0002] As a kind of engineering slag, only a small part of shield slag is used as synchronous grouting material after screening in China, and is used to make cast building materials, high-strength and high-density ceramsite, planting soil, etc. for resource utilization. Most of the shield slag is mainly treated by traditional open-air stacking or landfill, which not only occupies a large amount of land resources and deteriorates the urban environment, but also causes a large amount of sand, gravel, clay and other resources in the slag to be wasted. In addition, excessive slag stacking may cause disasters such as landslides. To solve these problems, it is necessary to develop an effective resource recycling method to achieve the goal of turning waste into treasure. Fluidized solidified soil is a backfill material widely used in various backfill projects, and has very low requirements for soil quality. Therefore, it is feasible to use engineering slag as raw material to make fluidized solidified soil. Soil particle grading has a very important influence on the physical and mechanical properties of the soil. Even if the soil is of the same soil quality, if the particle grading is different, its engineering properties will be quite different, especially for coarse-grained soil. There is no doubt that particle grading is one of the most important physical property indicators of soil. However, there is currently a lack of practice in the resource utilization of shield tunneling waste, resulting in poor performance of fluidized solidified soil in actual engineering, and failure to fully explore the potential of the waste, thus limiting its resource utilization.

[0003] There is a problem that fluidity, water seepage rate and compressive strength of fluidized solidified soil are difficult to coordinate. At present, the main methods to improve the fluidity of fluidized solidified soil are to increase the amount of water and add water reducing agent. However, these two methods will increase water seepage while improving the fluidity of fluidized solidified soil, thus reducing the stability of fluidized solidified soil.

[0004] As an inorganic non-metallic material, graphite plays an important role in the fields of electricity, chemical industry, national defense, etc. However, since a large amount of tailings will be left behind during the mining of graphite mines, especially in recent years, with the rapid mining of graphite mines, the amount of graphite tailings has increased sharply, causing serious pollution to the ecological environment.

[0005] At present, cement is mainly used as a cementing material for soil solidification. The production process of cement will cause a lot of pollution, so there is an urgent need to find a new green and environmentally friendly cementing material to replace cement. Alkali-activated solid waste-based cementing material is a green new material made of industrial waste and natural minerals. Using it as a soil solidifying agent is a development trend in the construction industry. This method has important engineering and environmental value and is expected to provide a feasible solution to the problem of shield soil treatment.

[0006] However, there are still some problems with alkali-activated cementitious materials. Graphite tailings, red mud, steel slag, fly ash, etc. have the problem of low activity. On the one hand, by optimizing the particle size range through ultrafine grinding, the activity of volcanic ash can be significantly improved, making it a satisfactory source of cementitious materials. On the other hand, the activity of cementitious materials can be stimulated by using strong alkalis such as sodium hydroxide and water glass. Although strong alkali activators can improve the mechanical properties of alkali-activated cementitious materials, they also bring problems such as high cost, high alkalinity causing alkali aggregate reaction and harm to the environment. Although the use of weak alkali activators solves many problems brought by strong alkali activators, the speed of promoting the dissolution of mineral phase is slow, resulting in insufficient excitation intensity, which leads to slow strength development of alkali-activated cementitious materials. However, organic alkali activators accelerate the dissolution of mineral phase ions by forming complexes with mineral phase ions, and generate stable coordination compounds, increase the ion concentration in the solution, and promote the formation of hydration products. As the mineral phase ions continue to be consumed, the organic alkali activator will continue to promote the dissolution of mineral phase ions and accelerate the strength development of cementitious materials. However, the cost of using organic alkali activators alone is high. Therefore, the combination of organic base activator and inorganic base activator can combine the advantages of both and solve the disadvantages of using only inorganic strong base activator and organic base activator. Summary of the invention

[0007] The purpose of the present invention is to provide a fluidized solidified soil with full particle size optimization based on the synergy of solid waste and slag and a preparation method thereof, by using alkali-activated solid waste-based cementitious materials as slag solidifying agents, cement is no longer used as a soil solidifying agent, thereby reducing energy consumption and carbon dioxide emissions, and at the same time using industrial solid wastes such as graphite tailings, red mud, slag powder, fly ash, and steel slag to reduce the storage of solid waste garbage and realize the resource utilization of shield slag and industrial solid waste. At the same time, the synergistic effect of composite thickeners, water reducers, foaming agents, and activated magnesium oxide solves the problem of difficulty in coordinating the fluidity of fluidized solidified soil with water seepage rate and compressive strength.

[0008] To achieve the above objectives, the present invention adopts the following technical solutions.

[0009] The solid waste-slag synergistic and full-particle-size optimized fluidized solidified soil is made of the following raw materials in parts by weight: ① 1512-1680 parts of full-particle-size optimized shield slag, including: extra coarse sand: 100-155 parts of 2-4 mesh shield sand; coarse sand: 150-185 parts of 4-10 mesh shield sand; medium sand: 200-260 parts of 10-18 mesh shield sand, 254 parts of 18-40 mesh shield sand; -308 parts; fine sand: 40-80 mesh shield sand 260-324 parts, 80-200 mesh shield sand 214-256 parts, 40-200 mesh graphite tailings 155-178 parts; extra fine sand: 200-400 mesh shield sand 130-180 parts; ② Full-particle size optimized solid waste-based cementitious materials 585-654 parts, including: modified graphite tailings 64-88, red mud a 20-25 parts, red mud b 30-42 parts, red mud c 60-83 parts, slag a 60-78 parts, slag b 95-127 parts, fly ash a 30-48 parts, fly ash b 64-89 parts, steel slag a 24-30 parts, steel slag b 30-36 parts, steel slag c52-67 powder; ③ 309-384 parts of mixing water, including 329-405 parts of shield wastewater, 4-6 parts of hydrated calcium silicate, 40-49 parts of deionized water, 1-1.5 parts of KH-570 silane coupling agent, 8-12 parts of anhydrous ethanol, 3-4 parts of cationic polyacrylamide with a mass fraction of 3%, and 6-9 parts of polyaluminium chloride; ④ 315-362 parts of composite alkali activator, including: 135-159 parts of sodium carbonate, 59-72 parts of sodium bicarbonate, 21-2 5 parts, deionized water 105-122 parts, methyldiethanolamine 1.2-2.4 parts, diisopropanolamine 2.2-3.8 parts, tetraethanolamine 1-1.8 parts, sodium lauryl sulfate 2.8-3.6 parts; ⑤ composite thickener 8-12 parts, including: cellulose ether 1.5-2.5 parts, starch ether 1.5-2.5 parts, bentonite 1.2-1.5 parts, deionized water 5-6 parts; ⑥ water reducer 7-9 parts; ⑦ foaming agent 7-9 parts; ⑧ active magnesium oxide 24-30 parts; ⑨ defoaming agent 12-15 parts. The raw material components are obtained through drying, crushing, ultrafine grinding and graded screening steps, and the particle size ranges of each component are: modified graphite tailings <75μm, red mud a <5μm, red mud b 5-20μm, red mud c 20-75μm, slag a 3-10μm, slag b 10-20μm, fly ash a <10μm, fly ash b 10-50μm.

[0010] Solid waste-slag synergy and full-particle size optimized fluidized solidified soil and preparation method, using secondary feeding process and specific mixing process, specifically including the following steps:

[0011] (1) Optimize the particle size of shield excavation soil. Use a screening machine or screen to screen out large-size coarse aggregate (>10 mm). Use a jaw crusher to crush the large-size coarse aggregate to a maximum particle size of less than 10 mm. Dehydrate the crushed excavation soil to make its moisture content ≤20%. Then grade and screen the excavation soil after dehydration.

[0012] (2) preparing modified graphite tailings, firstly performing high temperature activation, placing the graphite tailings in a high temperature furnace, controlling the heating rate of the calcining equipment at 10°C / min, and continuing calcining for 2 hours after reaching 750°C; cooling, after the high temperature calcination is completed, taking the graphite tailings out of the high temperature furnace and placing them in a ventilated indoor environment to cool for 1-2 hours; mechanical activation, performing secondary activation (mechanical activation) on the graphite tailings after high temperature activation, grinding them with a planetary ball mill at a rate of 500-800r / min for 5 hours;

[0013] (3) Prepare mixing water, add calcium silicate hydrate powder and deionized water into a beaker, and ultrasonically vibrate for 10-15 minutes at an ultrasonic power of 360W; after the ultrasonic vibration is completed, place the beaker in a constant temperature water bath and heat it to 90°C; dissolve KH-570 silane coupling agent in anhydrous ethanol, then slowly add it to the above beaker, and stir at a rate of 120-240r / min for 1.5-2h; after the reaction is completed, wash the sample with anhydrous ethanol for no less than 3 times, and then dry it to obtain modified calcium silicate hydrate; use a constant temperature water bath to heat the water bath to 90°C; dissolve KH-570 silane coupling agent in anhydrous ethanol, and then slowly add it to the above beaker, and stir at a rate of 120-240r / min for 1.5-2h; after the reaction is completed, wash the sample with anhydrous ethanol for no less than 3 times, and then dry it to obtain modified calcium silicate hydrate; Use a warm water bath to mature a 3% cationic polyacrylamide solution at 55-65°C for 1-1.5h; adjust the pH of the shield wastewater to 7 and the temperature to 30°C, then add modified calcium silicate hydrate, stir at 120-240r / min for 2-3min, then add the matured cationic polyacrylamide and polyaluminium chloride, stir at 120-240r / min for 4min; after stopping stirring, let it stand until the slurry is completely stratified, and take the supernatant as water for mixing the fluidised solidified soil.

[0014] (4) Mix the extra fine sand, fine sand and medium sand, and stir at a rate of 120-150 r / min for 2-3 min to obtain a uniform mixture I;

[0015] (5) mixing the modified graphite tailings, red mud, slag powder, fly ash and steel slag, and stirring at a rate of 120-150 r / min for 2-3 min to obtain a uniform mixture II;

[0016] (6) mixing the defoamer with part of the water, stirring at a rate of 200-300 r / min for 1-2 min, to obtain an additive solution I; mixing the water reducer with part of the water, stirring at a rate of 200-300 r / min for 1-2 min, to obtain an additive solution II; mixing the composite thickener with part of the water, stirring at a rate of 200-300 r / min for 1-2 min, to obtain an additive solution III; mixing the foaming agent with part of the water, stirring at a rate of 200-300 r / min for 1-2 min, to obtain an additive solution IV;

[0017] (7) Add water to half of the mixture, mix mixture I and mixture II, stir at a rate of 120-150 r / min for 1-2 min, and then stir at a rate of 200-300 r / min for 2-3 min to obtain a uniform slurry I;

[0018] (8) adding a composite alkali activator to slurry I, stirring at a rate of 120-150 r / min for 2-3 min, to obtain slurry II;

[0019] (9) Add coarse sand, extra coarse sand and the remaining mixing water to slurry II, stir at a rate of 120-150 r / min for 1-2 min, and then stir at a rate of 200-300 r / min for 2-3 min to obtain a uniform slurry III;

[0020] (10) Adding additive solution I, additive solution II, additive solution III and additive solution IV to slurry III, stirring at a rate of 200-300 r / min for 2-3 min to obtain a uniform slurry IV;

[0021] (11) Add active magnesium oxide to the uniform slurry IV and stir at a rate of 200-300 r / min for 2-3 min to obtain fluidized solidified soil with solid waste-slag synergy and full particle size optimization.

[0022] Furthermore, in step (1), the shield slag obtained after dehydration treatment is graded and screened, wherein the first-level vibrating screen selected in the first-level screening treatment is a 2-mesh screen, the second-level vibrating screen selected in the second-level screening treatment is a 4-mesh screen, the third-level vibrating screen selected in the third-level screening treatment is a 10-mesh screen, the fourth-level vibrating screen selected in the fourth-level screening treatment is an 18-mesh screen, the fifth-level vibrating screen selected in the fifth-level screening treatment is a 40-mesh screen, the sixth-level vibrating screen selected in the sixth-level screening treatment is an 80-mesh screen, the seventh-level vibrating screen selected in the seventh-level screening treatment is a 200-mesh screen, and the eighth-level vibrating screen selected in the eighth-level screening treatment is a 400-mesh screen.

[0023] Furthermore, the shield wastewater is muddy wastewater obtained after dehydration treatment in step (1), and its mud content is less than 15%, and its organic matter content is less than 5%.

[0024] Furthermore, the foaming agent is prepared by diluting a rosin-type plant foaming agent with water at a ratio of 1:50 and then foaming the foaming agent, and the density is 45-60 kg / m 3 .

[0025] Furthermore, the purity of sodium sulfate is ≥99.5%, the purity of sodium carbonate is ≥99.0%, the purity of sodium bicarbonate is ≥99.5%, the purity of methyldiethanolamine is ≥95.0%, the purity of diisopropanolamine is ≥99.0%, the purity of tetraethanolamine is ≥99.5%, and the purity of sodium dodecyl sulfate is ≥99.5%.

[0026] Furthermore, the composite base activator is prepared by the following steps:

[0027] (1) Sodium sulfate, sodium carbonate, sodium bicarbonate and deionized water are stirred at a rate of 120-150 r / min for 2-3 min, the resulting mixture is passed through a 400-mesh sieve, and the sieved slurry is collected to obtain an inorganic base activator;

[0028] (2) heating the inorganic alkali solution to 35-45° C., then adding methyldiethanolamine, diisopropanolamine and tetraethanolamine thereto at the same time and stirring and mixing at a rate of 200-300 r / min for 3-5 min;

[0029] (3) adding sodium dodecyl sulfate to the solution obtained in step (3) and stirring the mixture at a rate of 300-500 r / min for 2-3 min to obtain a composite alkali activator.

[0030] Furthermore, the composite thickener is prepared by the following steps:

[0031] (1) Heat to dissolve: heat deionized water to 60-80° C., then slowly add cellulose ether into the water and stir at a rate of 200-300 r / min for 4-6 min;

[0032] (2) adding starch ether, lowering the temperature to 40-60° C., gradually adding starch ether to the mixture obtained in step (1), and stirring at a rate of 200-300 r / min for 3-5 min;

[0033] (3) adding bentonite, gradually adding bentonite to the mixture obtained in step (2), stirring at a rate of 600-900 r / min for 7-10 min, and controlling the temperature at 40-60° C.;

[0034] (4) filtering and removing bubbles, filtering the mixture obtained in step (3) through a membrane filter to remove bubbles and impurities therein, wherein the pore size of the filter is in the range of 0.2-5 μm;

[0035] (5) Adjusting the pH value: adding sodium hydroxide solution to the mixture obtained in step (4) to adjust the pH value to 7-9, thereby obtaining a composite thickener.

[0036] Furthermore, the red mud before grinding complies with the provisions of the national standard GB50986-2014; the slag before grinding is S95 grade slag that complies with the national standard GB / T18046-2008; the fly ash before grinding is Class II fly ash that complies with the national standard GB / T1596-2017; the steel slag before grinding complies with the provisions of the national standard GB / T20491-2017; the cationic polyacrylamide complies with the national The polyaluminium chloride complies with the provisions of the national standard GB / T31246-2014; the polyaluminium chloride complies with the provisions of the national standard GB / T22627-2022; the cellulose ether is hydroxypropyl methylcellulose that complies with the national standard GB / T34263-2017, with a viscosity of 100,000 mP·S and a fineness of 18% (300 mesh square hole sieve residue); the starch ether is carboxymethyl starch that complies with the national standard GB / T20375-2006, with a viscosity of 10,000 m SP, fineness is 17% (300 mesh square hole sieve residue); the bentonite is sodium bentonite that complies with the national standard GB / T20973-2020, with a 2h water absorption rate of ≤150%, and a fineness of 6.5% (300 mesh square hole sieve residue); the water reducer is a polycarboxylic acid high-performance water reducer that complies with the provisions of the national standard GB8076-2008; the defoamer is a silicone defoamer that complies with the national standard GB / T26527-2011; the foaming agent is a rosin-type plant foaming agent that complies with the national standard GB / T35140-2017; the magnesium oxide content in the active magnesium oxide is 95%, and the density is 3.85g / cm 3 , white powder, in compliance with the provisions of standard HG / T3928-2007; the sodium sulfate complies with the provisions of national standard GB29209-2012; the sodium bicarbonate is industrial grade sodium bicarbonate in compliance with national standard GB / T 1606-2008; the sodium sulfate is industrial anhydrous sodium sulfate in compliance with national standard GB / T 6009-2014; the deionized water is grade III pure water in compliance with national standard GB 6682-2012; the tetraethanolamine complies with the provisions of standard HG / T2915-1997; and the sodium dodecyl sulfate complies with the provisions of national standard GB / T 15963-2022.

[0037] Furthermore, the solid waste-slag synergistic and full-particle-size optimized fluidized solidified soil can be used for backfill pouring of various fertilizer troughs, foundation pits, municipal pipelines, mines, shield wall backspace and other projects. It can also be used in road subgrades, building foundations, hydraulic geotechnical engineering, marine geotechnical engineering and other reinforcement fields.

[0038] Compared with the prior art, the present invention brings the following beneficial technical effects:

[0039] (1) As a kind of engineering slag, shield slag is currently mainly treated in China by traditional open-air stacking or landfilling. Only a small part of it is recycled, and it is necessary to carry out complex processes such as on-site slurry-slag separation, mud-water separation, and water purification to separate the shield slag into sand and gravel aggregates, water, and dried soil. In addition, the utilization of shield slag has not been optimized for particle size, so that its physical and mechanical properties cannot be fully utilized. The present invention subjects the shield slag to eight-level screening treatment to obtain "locally concentrated, overall dispersed" full-particle-size optimized shield slag, which improves the workability and bearing capacity of the fluidized solidified soil. Among them, the coarse aggregate plays a role as a skeleton, mainly improving the strength and stability, and is the main source of strength. The fine aggregate can fill the gaps and improve the density of the material.

[0040] (2) At present, while improving the fluidity of fluidized solidified soil, it is often accompanied by the problem of increased water seepage rate and reduced compressive strength, and the traditional method of adding water reducer and increasing water consumption can only improve the fluidity of fluidized solidified soil. Based on this, the present invention has made innovations in formula and method. By adding composite thickener, water reducer, foaming agent and activated magnesium oxide, the fluidized solidified soil can have fluidity, stability and self-compactness while improving its compressive strength, thereby solving the problem that the fluidity of fluidized solidified soil is difficult to coordinate with its compressive strength and water seepage rate. Cellulose ether is a thickener with a colloidal structure, which can quickly form a lubricating film in the fluidized solidified soil slurry, accelerate the fusion between soil and cementitious materials, and act as a lubricant, thereby improving the working performance and construction performance of the fluidized solidified soil. At the same time, the molecular structure of cellulose ether can absorb moisture on the surface of soil particles and cementitious materials, prevent the rapid loss of moisture in the slurry, and thus improve the water retention of the mortar. Starch ether is a substituent ether, which is generally generated by the reaction of hydroxyl groups in the molecule with active substances. It has good thickening ability. A small amount of starch ether added to the fluidized solidified soil can achieve a good effect and can replace part of the cellulose ether. Bentonite is mainly composed of montmorillonite and other phases, with a layered structure and strong water absorption and expansion, and the expansion volume can reach 20 times its own volume. In the fluidized solidified soil, bentonite can absorb excess water, and the gelling material in the slurry will release a certain amount of heat during the hydration reaction. This heat will cause the water absorbed by the bentonite to be released, thereby slowing down the evaporation and loss of water and improving the water retention effect of the slurry. In addition, bentonite can also weaken the interaction between cellulose ether molecules, improve the thixotropy of mortar, and reduce the adhesion of mortar on operating tools. Therefore, bentonite is an effective supplement to cellulose. Through the synergistic effect of the three, the advantages are complementary, and the problems of high price, poor thixotropy, and adhesion of slurry to operating tools of a single water-retaining thickener are solved, thereby improving the water retention, cohesion and fluidity of the slurry.

[0041] (3) The main chemical components of graphite tailings include SiO2, Al2O3, Fe2O3 and CaO, among which the SiO2 content is as high as 55%. However, SiO2 exists in the form of quartz crystals, which makes the natural graphite tailings very low in activity and difficult to use directly. However, the volcanic ash activity of graphite tailings can be stimulated by high-temperature calcination and mechanical grinding. High-temperature calcination can cause the crystalline SiO2 in the graphite tailings to undergo an amorphous transformation, thereby stimulating its volcanic ash activity. Calcination temperatures above 650°C can effectively activate graphite tailings, and as the calcination temperature increases, the activity stimulation effect of graphite tailings is further improved. A calcination temperature of 750°C can significantly increase the volcanic ash activity of graphite tailings. At the same time, the high-temperature calcination process consumes the residual carbon in the graphite tailings, which helps to further improve its activity. The graphite tailings after high-temperature activation are secondary activated (mechanically activated) and ground by a planetary ball mill. The median particle size D of the ground graphite tailings is 2.347 W / m2. 50 =12μm, specific surface area is 492m 2 / kg, the volcanic ash activity is further stimulated.

[0042] (4) Since the hydration degree and activity index of coarse-grained red mud are low at 3 days and 28 days, the activity of the red mud after grinding is greatly improved. Under the action of alkali excitation, the activity of red mud with a particle size of less than 5μm reaches the highest. SiO2, Al2O3 and other components in red mud particles can react with components in steel slag, slag, and fly ash to form CSH and CASH gels, thereby improving the mechanical properties of the slurry. Although the early activity of red mud particles with a particle size of 5-20μm is lower than that of red mud with a particle size of less than 5μm, its later activity is higher, which is conducive to the improvement of later strength. The activity of red mud with a particle size of 20-75μm is relatively low, and most of it does not react, but it can effectively fill the voids in the slurry and play the role of supporting the skeleton of the cementitious material, thereby improving the density of the slurry structure.

[0043] Since the slag with a particle size of 3-10μm has a large specific surface area and extremely high hydration activity, most of its hydration reactions occur within 3 days, and the amount of hydration products generated in the later stage is small, which makes the slurry structure unable to be further compacted, resulting in a limited 28-day activity index of the slag in this particle size range. However, the slag with a particle size of 10-20μm has a high degree of hydration in 28 days, and a large amount of hydration products fill the pores of the slurry, making the slurry structure very dense.

[0044] Due to the phase separation phenomenon in the grinding process of fly ash, the fly ash with a particle size of 10-50μm has a higher content of crystalline minerals, while the fly ash with a particle size of less than 10μm has a higher content of carbon, alkali, SO3 and glass. Glass is the main source of fly ash volcanic ash activity, and SO3 and alkali can effectively stimulate the volcanic ash activity of fly ash. The sphericity of fly ash with a particle size of less than 10μm is better, and it is mainly composed of spherical particles with smooth surfaces; the sphericity of fly ash with a particle size of 10-50μm is also better, and it is mainly composed of smooth spherical particles and porous and irregular particles, which makes it more conducive to the ball effect at the microscopic level, thereby significantly improving the fluidity of the slurry.

[0045] During the grinding process, there is a significant phase separation phenomenon in steel slag. Although the calcium-silicon ratio of steel slag with a particle size less than 3μm is relatively low, calcium mostly exists in the form of silicate. The C2S and C3S content of steel slag in this particle size range increases significantly, and the total amount of silicate minerals in steel slag is as high as 65.0%, which greatly improves the hydration reaction rate of steel slag. Although the early hydration degree of steel slag with a particle size of 3-10μm is low, its 28d hydration degree can reach more than 50%, which is conducive to the improvement of later strength. The 3d and 28d hydration degrees of steel slag with a particle size of 10-20μm are both low, and only surface hydration occurs, but steel slag in this particle size range can fill the gaps between red mud particles with a particle size of 20-75μm.

[0046] The full-size optimized solid waste-based cementitious materials are used, cement is no longer used as a curing agent, and energy consumption and carbon dioxide emissions are reduced. The fluidized solidified soil has the advantages of high density, good fluidity, low water seepage rate and high curing strength. It can be used for backfilling and pouring of various fertilizer troughs, foundation pits, municipal pipelines, and mines. It can also be used in reinforcement fields such as roadbeds and building foundations, realizing the resource reuse of shield slag and providing a practical solution for the treatment of shield slag.

[0047] (5) At present, the alkali activators used to prepare fluidized solidified soil are mostly strong alkali activators such as water glass and sodium hydroxide. However, while strong alkali activators enable cementitious materials to have better mechanical properties, they can also cause problems such as excessive alkalinity, alkali-aggregate reaction, and environmental damage. The composite alkali activator provided by the present invention has a lower alkalinity, which solves the problems caused by strong alkali activators. The inorganic weak alkali activator and the organic alkali activator can be combined to synergistically promote the dissolution of the mineral phase. The organic alkali activator can accelerate the dissolution of the mineral phase by complexing with the mineral phase ions and generate stable coordination compounds, thereby promoting the crystallization growth process of the hydration product and achieving an activating effect equivalent to that of the strong alkali activator.

[0048] (6) For the traditional preparation method of fluidized solidified soil, if the uniformity of the newly mixed fluidized solidified soil is affected, it will cause the problem of uneven strength distribution. When bearing load, this will easily lead to damage in the fragile area of ​​the fluidized solidified soil, thereby reducing the durability of the overall structure. In contrast, the present invention provides a new preparation process, which adopts a secondary feeding process and a specific mixing process, the key of which is to achieve uniform dispersion of cementitious materials and slag in each particle size range in a relatively short time. This innovative preparation process helps to construct a solid waste-based cementitious system based on full particle size optimization, thereby forming a newly mixed fluidized solidified soil with uniformity and stability, so that it is more uniformly stressed when bearing load, thereby improving the bearing capacity and durability of the overall structure. At the same time, compared with the traditional preparation process, the 7-day strength increased by an average of 15%, and the 28-day strength increased by 22%. The use of the secondary feeding process reduces the discreteness of the 28-day strength, and its strength mean square error is 23%, and the discreteness rate is 7.5%. The workability of the fluidized solidified soil is also improved, and it is not easy to produce segregation and bleeding, thereby improving the stability of the fluidized solidified soil. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] The present invention will be further described below in conjunction with the accompanying drawings:

[0050] Figure 1 The present invention is a process flow chart for preparing fluidized solidified soil. DETAILED DESCRIPTION

[0051] The technical solution of the present invention will be described in detail below in conjunction with specific embodiments. It should be clear that the embodiments provided in the present invention only represent a part of the examples of the present invention and do not represent all the examples. According to the examples provided in the present invention, ordinary technicians in the field can develop other embodiments without violating the spirit and scope of the present invention.

[0052] The raw materials described in the present invention can be purchased through commercial channels.

[0053] The structure and working principle of the vibrating screen described in the present invention can be realized by referring to the prior art.

[0054] In the following embodiments and comparative examples, the red mud before grinding complies with the provisions of the national standard GB50986-2014; the slag before grinding is S95 grade slag that complies with the national standard GB / T18046-2008; the fly ash before grinding is Class II fly ash that complies with the national standard GB / T1596-2017; the steel slag before grinding complies with the provisions of the national standard GB / T20491-2017; the cationic polyacrylamide complies with the national standard GB / T 31246-2014; the polyaluminium chloride complies with the provisions of the national standard GB / T22627-2022; the cellulose ether is hydroxypropyl methylcellulose that complies with the national standard GB / T34263-2017, with a viscosity of 100,000 mP·S and a fineness of 18% (300 mesh square hole sieve residue); the starch ether is carboxymethyl starch that complies with the national standard GB / T20375-2006, with a viscosity of 10,000 m SP, fineness is 17% (300 mesh square hole sieve residue); the bentonite is sodium bentonite that complies with the national standard GB / T20973-2020, with a 2h water absorption rate of ≤150%, and a fineness of 6.5% (300 mesh square hole sieve residue); the water reducer is a polycarboxylic acid high-performance water reducer that complies with the provisions of the national standard GB8076-2008; the defoamer is a silicone defoamer that complies with the national standard GB / T26527-2011; the foaming agent is a rosin-type plant foaming agent that complies with the national standard GB / T35140-2017; the magnesium oxide content in the active magnesium oxide is 95%, and the density is 3.85g / cm 3 , white powder, in compliance with the provisions of standard HG / T3928-2007; the sodium sulfate complies with the provisions of national standard GB 29209-2012; the sodium bicarbonate is industrial grade sodium bicarbonate in compliance with national standard GB / T 1606-2008; the sodium sulfate is industrial anhydrous sodium sulfate in compliance with national standard GB / T 6009-2014; the deionized water is grade III pure water in compliance with national standard GB 6682-2012; the tetraethanolamine complies with the provisions of standard HG / T2915-1997; and the sodium dodecyl sulfate complies with the provisions of national standard GB / T 15963-2022.

[0055] Example 1

[0056] The fluidized solidified soil with solid waste-slag synergy and full-particle size optimization and its preparation method are made of the following raw materials in parts by weight: 1584 parts of full-particle size optimized shield slag; 624 parts of full-particle size optimized solid waste-based cementitious materials; 350 parts of mixing water; 350 parts of composite alkali activator; 10.5 parts of composite thickener; 7 parts of water reducer; 8 parts of foaming agent; 24 parts of active magnesium oxide; and 13 parts of defoaming agent.

[0057] Preferably, the full-particle size optimized shield slag is made of the following raw materials in parts by weight: 120 parts of 2-4 mesh shield sand, 162 parts of 4-10 mesh shield sand, 236 parts of 10-18 mesh shield sand, 277 parts of 18-40 mesh shield sand, 275 parts of 40-80 mesh shield sand, 216 parts of 80-200 mesh shield sand, 156 parts of 40-200 mesh graphite tailings, and 142 parts of 200-400 mesh shield sand.

[0058] Preferably, the full-particle size optimized solid waste-based cementitious material is made of the following raw materials in parts by weight: 72 parts of modified graphite tailings, 20 parts of red mud a, 35 parts of red mud b, 75 parts of red mud c, 67 parts of slag a, 112 parts of slag b, 39 parts of fly ash a, 78 parts of fly ash b, 30 parts of steel slag a, 34 parts of steel slag b, and 62 parts of steel slag c.

[0059] Solid waste-slag synergy and full-particle size optimized fluidized solidified soil and preparation method, using secondary feeding process and specific mixing process, specifically including the following steps:

[0060] (1) Optimize the particle size of shield excavation soil. Use a screening machine or screen to screen out large-size coarse aggregate (>10 mm). Use a jaw crusher to crush the large-size coarse aggregate to a maximum particle size of less than 10 mm. Dehydrate the crushed excavation soil to make its moisture content ≤20%. Then grade and screen the excavation soil after dehydration.

[0061] (2) preparing modified graphite tailings, firstly performing high temperature activation, placing the graphite tailings in a high temperature furnace, controlling the heating rate of the calcining equipment at 10°C / min, and continuing calcining for 2 hours after reaching 750°C; cooling, after the high temperature calcination is completed, taking the graphite tailings out of the high temperature furnace and placing them in a ventilated indoor environment to cool for 1-2 hours; mechanical activation, performing secondary activation (mechanical activation) on the graphite tailings after high temperature activation, grinding them with a planetary ball mill at a rate of 500-800r / min for 5 hours;

[0062] (3) Prepare mixing water, add calcium silicate hydrate powder and deionized water into a beaker, and ultrasonically vibrate for 10-15 minutes at an ultrasonic power of 360W; after the ultrasonic vibration is completed, place the beaker in a constant temperature water bath and heat it to 90°C; dissolve KH-570 silane coupling agent in anhydrous ethanol, then slowly add it to the above beaker, and stir at a rate of 120-240r / min for 1.5-2h; after the reaction is completed, wash the sample with anhydrous ethanol for no less than 3 times, and then dry it to obtain modified calcium silicate hydrate; use a constant temperature water bath to heat the water bath to 90°C; dissolve KH-570 silane coupling agent in anhydrous ethanol, and then slowly add it to the above beaker, and stir at a rate of 120-240r / min for 1.5-2h; after the reaction is completed, wash the sample with anhydrous ethanol for no less than 3 times, and then dry it to obtain modified calcium silicate hydrate; Use a warm water bath to mature a 3% cationic polyacrylamide solution at 55-65°C for 1-1.5h; adjust the pH of the shield wastewater to 7 and the temperature to 30°C, then add modified calcium silicate hydrate, stir at 120-240r / min for 2-3min, then add the matured cationic polyacrylamide and polyaluminium chloride, stir at 120-240r / min for 4min; after stopping stirring, let it stand until the slurry is completely stratified, and take the supernatant as water for mixing the fluidised solidified soil.

[0063] (4) Mix the extra fine sand, fine sand and medium sand, and stir at a rate of 120-150 r / min for 2-3 min to obtain a uniform mixture I;

[0064] (5) mixing the modified graphite tailings, red mud, slag powder, fly ash and steel slag, and stirring at a rate of 120-150 r / min for 2-3 min to obtain a uniform mixture II;

[0065] (6) mixing the defoamer with part of the water, stirring at a rate of 200-300 r / min for 1-2 min, to obtain an additive solution I; mixing the water reducer with part of the water, stirring at a rate of 200-300 r / min for 1-2 min, to obtain an additive solution II; mixing the composite thickener with part of the water, stirring at a rate of 200-300 r / min for 1-2 min, to obtain an additive solution III; mixing the foaming agent with part of the water, stirring at a rate of 200-300 r / min for 1-2 min, to obtain an additive solution IV;

[0066] (7) Add water to half of the mixture, mix mixture I and mixture II, stir at a rate of 120-150 r / min for 1-2 min, and then stir at a rate of 200-300 r / min for 2-3 min to obtain a uniform slurry I;

[0067] (8) adding a composite alkali activator to slurry I, stirring at a rate of 120-150 r / min for 2-3 min, to obtain slurry II;

[0068] (9) Add coarse sand, extra coarse sand and the remaining mixing water to slurry II, stir at a rate of 120-150 r / min for 1-2 min, and then stir at a rate of 200-300 r / min for 2-3 min to obtain a uniform slurry III;

[0069] (10) Adding additive solution I, additive solution II, additive solution III and additive solution IV to slurry III, stirring at a rate of 200-300 r / min for 2-3 min to obtain a uniform slurry IV;

[0070] (11) Add active magnesium oxide to the uniform slurry IV and stir at a rate of 200-300 r / min for 2-3 min to obtain fluidized solidified soil with synergistic effects of solid waste and slag and optimized particle size.

[0071] Preferably, in step (1), the shield slag obtained after dehydration treatment is graded and screened, wherein the first-level vibrating screen selected in the first-level screening treatment is a 2-mesh screen, the second-level vibrating screen selected in the second-level screening treatment is a 4-mesh screen, the third-level vibrating screen selected in the third-level screening treatment is a 10-mesh screen, the fourth-level vibrating screen selected in the fourth-level screening treatment is an 18-mesh screen, the fifth-level vibrating screen selected in the fifth-level screening treatment is a 40-mesh screen, the sixth-level vibrating screen selected in the sixth-level screening treatment is an 80-mesh screen, the seventh-level vibrating screen selected in the seventh-level screening treatment is a 200-mesh screen, and the eighth-level vibrating screen selected in the eighth-level screening treatment is a 400-mesh screen.

[0072] Preferably, the shield wastewater is the muddy wastewater obtained after dehydration treatment in step (1), and the mud content is less than 15% and the organic matter content is less than 5%.

[0073] Preferably, the particle size range of each component of the solid waste-based cementitious material is optimized, modified graphite tailings <75μm, red mud a <5μm, red mud b 5-20μm, red mud c 20-75μm, slag a 3-10μm, slag b10-20μm, fly ash a <10μm, fly ash b 10-50μm, steel slag a <3μm, steel slag b 3-10μm, steel slag c 10-20μm.

[0074] Preferably, the foaming agent is prepared by diluting a rosin-type plant foaming agent with water at a ratio of 1:50 and foaming the foam, and the density is 45-60 kg / m 3 .

[0075] Preferably, the purity of sodium sulfate is ≥99.5%, the purity of sodium carbonate is ≥99.0%, the purity of sodium bicarbonate is ≥99.5%, the purity of methyldiethanolamine is ≥95.0%, the purity of diisopropanolamine is ≥99.0%, the purity of tetraethanolamine is ≥99.5%, and the purity of sodium dodecyl sulfate is ≥99.5%.

[0076] Preferably, the composite base activator is prepared by the following steps:

[0077] (1) 21 parts of sodium sulfate, 150 parts of sodium carbonate, 65 parts of sodium bicarbonate and 108 parts of deionized water are stirred at a rate of 120-150 r / min for 2-3 minutes, the resulting mixture is passed through a 400-mesh sieve, and the sieved slurry is collected to obtain an inorganic base activator;

[0078] (2) The inorganic alkali solution is heated to 35-45° C., and then 1.6 parts of methyldiethanolamine, 3.2 parts of diisopropanolamine and 1.2 parts of tetraethanolamine are added thereto at the same time and stirred for mixing at a rate of 200-300 r / min for 3-5 min.

[0079] (3) Add 3 parts of sodium dodecyl sulfate to the solution obtained in step (3) and stir to mix, and stir at a rate of 300-500 r / min for 2-3 min to obtain a composite alkali activator.

[0080] Preferably, the composite thickener is prepared by the following steps:

[0081] (1) Heat to dissolve: heat 5 parts of deionized water to 60-80°C, then slowly add 2 parts of cellulose ether into the water and stir at a rate of 200-300 r / min for 4-6 minutes.

[0082] (2) Add starch ether, lower the temperature to 40-60° C., gradually add 2 parts of starch ether to the mixture obtained in step (1), and stir at a rate of 200-300 r / min for 3-5 min.

[0083] (3) Adding bentonite: gradually add 1.5 parts of bentonite to the mixture obtained in step (2), stir at a speed of 600-900 r / min for 7-10 min, and control the temperature at 40-60°C.

[0084] (4) Filtering and removing bubbles: filtering the mixture obtained in step (4) through a membrane filter to remove bubbles and impurities therein, wherein the pore size of the filter is in the range of 0.2-5 μm.

[0085] (5) Adjusting the pH value: adding sodium hydroxide solution to the mixture obtained in step (5) to adjust the pH value to 7-9, thereby obtaining a composite thickener.

[0086] Preferably, the solid waste-slag synergistic and full-particle-size optimized fluidized solidified soil can be used for backfill pouring of various fertilizer troughs, foundation pits, municipal pipelines, mines, shield wall backspace and other projects, and can also be used in road subgrades, building foundations, hydraulic geotechnical engineering, marine geotechnical engineering and other reinforcement fields.

[0087] The finished fluidized solidified soil is tested for fluidity, water seepage rate and unconfined compressive strength, as follows:

[0088] (1) Fluidity test

[0089] The specific measurement method of the flow value is as follows: prepare a glass plate with a smooth surface and place it on a horizontal plane. Select a glass cylinder with an upper and lower opening of 8 cm in diameter and 8 cm in height as a container for the fluidized solidified soil. Wipe the surface of the glass plate and the inner wall of the cylinder with a wet towel, and then place the cylinder in the center of the glass plate. Fill the cylinder with fluidized solidified soil so that the edge of the liquid surface is flush with the edge of the cylinder. Pinch the outer wall of the cylinder with both hands and quickly lift it vertically upward to allow the double liquid slurry A to diffuse freely on the glass plate for 30 seconds. Then use a ruler with a scale of 1 mm to measure the maximum and minimum diameters of the diffusion surface, and take the average value as the fluidity. In order to ensure the reliability of the test, each group of samples needs to be tested in parallel 3 times, and the average value is taken as the final flow value;

[0090] (2) Water seepage rate test

[0091] The water bleeding rate refers to the proportion of water precipitated by the slurry due to the sedimentation of powder particles in a static state, and is an important indicator for evaluating the stability of the slurry. In this test, first, take 90mL of the prepared fresh slurry and place it in a 100mL clean measuring cylinder, which is sealed with plastic film. Then, place the measuring cylinder on the test bench. As time goes by, the suspended particles begin to sink and the volume of the upper water gradually increases. Finally, read and record the volume of the supernatant at 2h. The water bleeding rate can be calculated according to the following formula.

[0092]

[0093] Where V0 is the supernatant volume (mL), and V is the total grouting volume (mL).

[0094] (3) Unconfined compressive strength test

[0095] The unconfined compressive strength test is carried out in accordance with the Geotechnical Test Method Standard (GB / T50123-2019). The sample size is Ф39.1mm×80mm. It is placed in a curing box with a humidity of 95% and a temperature of (20±2)℃ for curing. After curing to the specified age, the unconfined compressive strength test is carried out with a compression rate of 1.18mm / min. In order to ensure the reliability of the test, each group of samples needs to be tested in parallel three times, and the average value is taken as the final unconfined compressive strength.

[0096] Example 2

[0097] The fluidized solidified soil with solid waste-slag synergy and full-particle size optimization was prepared according to the method of Example 1, except that the proportion of all-solid waste-based cementitious materials was as follows: 80 parts of modified graphite tailings, 20 parts of red mud a, 40 parts of red mud b, 80 parts of red mud c, 65 parts of slag a, 120 parts of slag b, 40 parts of fly ash a, 80 parts of fly ash b, 30 parts of steel slag a, 35 parts of steel slag b, and 65 parts of steel slag c, totaling 655 parts.

[0098] Comparative Example 1

[0099] The fluidized solidified soil with solid waste-slag synergy and full-particle size optimization was prepared according to the method of Example 1, except that the shield slag used was not subjected to full-particle size optimization and secondary feeding.

[0100] Comparative Example 2

[0101] The solid waste-slag synergistic and full-particle-size optimized fluidized solidified soil was prepared according to the method of Example 1, except that the solid waste-based cementitious material used was not optimized for full particle size.

[0102] Comparative Example 3

[0103] The solid waste-slag synergistic and full-particle-size optimized fluidized solidified soil was prepared according to the method of Example 1, except that no composite thickener was added.

[0104] Comparative Example 4

[0105] The solid waste-slag synergistic and full-particle-size optimized fluidized solidified soil was prepared according to the method of Example 1, except that no foaming agent was added.

[0106] Comparative Example 5

[0107] The solid waste-slag synergistic and full-particle-size optimized fluidized solidified soil was prepared according to the method of Example 1, except that no active magnesium oxide was added.

[0108] Comparative Example 6

[0109] The solid waste-slag synergistic and full-particle-size optimized fluidized solidified soil was prepared according to the method of Example 1, except that the cementitious material was PO 2.5 cement.

[0110] The above examples are only used to illustrate the technical concept and features of the present invention, and are intended to help relevant technical personnel in the field understand the content of the present invention and serve as a reference for implementation, and are not intended to limit the scope of protection of the present invention. Any equivalent changes or modifications made based on the spirit of the present invention should be deemed to fall within the scope of protection of the present invention.

Claims

1. A method for preparing fluidized solidified soil with synergistic solid waste and soil slag and full particle size optimization, characterized in that: The invention is made of the following raw materials in parts by weight: ① 1512-1680 parts of full-particle-size optimized shield slag, including: extra-coarse sand: 100-155 parts of 2-4 mesh shield sand; coarse sand: 150-185 parts of 4-10 mesh shield sand; medium sand: 200-260 parts of 10-18 mesh shield sand, 254-308 parts of 18-40 mesh shield sand; fine sand: 260-324 parts of 40-80 mesh shield sand, 214-256 parts of 80-200 mesh shield sand, 155-178 parts of 40-200 mesh graphite tailings; extra-fine sand: 130-180 parts of 200-400 mesh shield sand; ② 585-654 parts of full-particle-size optimized solid waste-based cementitious materials, including: 64-88 parts of modified graphite tailings, 20-25 parts of red mud a, 20-25 parts of red mud b 30-42 parts, red mud c 60-83 parts, slag a 60-78 parts, slag b 95-127 parts, fly ash a 30-48 parts, fly ash b 64-89 parts, steel slag a 24-30 parts, steel slag b 30-36 parts, steel slag c 52-67 parts; ③ 309-384 parts of mixing water, including 329-405 parts of shield wastewater, 4-6 parts of calcium silicate hydrate, 40-49 parts of deionized water, 1-1.5 parts of KH-570 silane coupling agent, 8-12 parts of anhydrous ethanol, 3-4 parts of cationic polyacrylamide with a mass fraction of 3%, and 6-9 parts of polyaluminium chloride; ④ 315-362 parts of composite alkali activator, including: 135-159 parts of sodium carbonate, 59-72 parts of sodium bicarbonate, 21-25 parts of sodium sulfate, 105-122 parts of deionized water, 1.2-2.4 parts of methyldiethanolamine, and diisopropanolamine ⑤ 8-12 parts of composite thickener, including: 1.5-2.5 parts of cellulose ether, 1.5-2.5 parts of starch ether, 1.2-1.5 parts of bentonite, 5-6 parts of deionized water; ⑥ 7-9 parts of water reducer; ⑦ 7-9 parts of foaming agent; ⑧ 24-30 parts of active magnesium oxide; ⑨ 12-15 parts of defoamer; the raw material components are obtained through drying, crushing, ultrafine grinding and graded screening steps, and the particle size ranges of each component are: modified graphite tailings <75μm, red mud a <5μm, red mud b 5-20μm, red mud c 20-75μm, slag a 3-10μm, slag b 10-20μm, fly ash a<10μm, fly ash b 10-50μm, steel slag a<3μm, steel slag b 3-10μm, steel slag c 10-20μm; adopting secondary feeding process and specific mixing process, specifically including the following steps: (1) Optimize the particle size of shield excavation soil. Use a screening machine or screen to screen out coarse aggregate with a large particle size of >10 mm. Use a jaw crusher to crush the coarse aggregate with a large particle size to a maximum particle size of less than 10 mm. Dehydrate the crushed excavation soil to make its moisture content ≤20%. Then grade and screen the excavation soil obtained after dehydration. (2) preparing modified graphite tailings, firstly performing high temperature activation, placing the graphite tailings in a high temperature furnace, controlling the heating rate of the calcining equipment at 10°C / min, and continuing calcining for 2 hours after reaching 750°C; cooling, after the high temperature calcination is completed, taking the graphite tailings out of the high temperature furnace and placing them in a ventilated indoor environment to cool for 1-2 hours; mechanical activation, performing secondary activation on the graphite tailings after high temperature activation, grinding them with a planetary ball mill, and grinding them at a rate of 500-800r / min for 5 hours; (3) Prepare mixing water, add calcium silicate hydrate powder and deionized water into a beaker, and ultrasonically vibrate for 10-15 minutes at an ultrasonic power of 360W; after the ultrasonic vibration is completed, place the beaker in a constant temperature water bath and heat it to 90°C; dissolve KH-570 silane coupling agent in anhydrous ethanol, then slowly add it to the above beaker, and stir at a rate of 120-240r / min for 1.5-2h; after the reaction is completed, wash the sample with anhydrous ethanol for no less than 3 times, and then dry it to obtain modified calcium silicate hydrate; use a constant temperature water bath to heat the water bath to 90°C; dissolve KH-570 silane coupling agent in anhydrous ethanol, and then slowly add it to the above beaker, and stir at a rate of 120-240r / min for 1.5-2h; after the reaction is completed, wash the sample with anhydrous ethanol for no less than 3 times, and then dry it to obtain modified calcium silicate hydrate; A 3% cationic polyacrylamide solution is matured at 55-65°C in a warm water bath for 1-1.5h; the pH of the shield wastewater is adjusted to 7 and the temperature is adjusted to 30°C, and then modified calcium silicate hydrate is added, and stirred at a rate of 120-240r / min for 2-3min, and then the matured cationic polyacrylamide and polyaluminium chloride are added, and stirred at a rate of 120-240r / min for 4min; after stopping stirring, the slurry is allowed to stand until it is completely separated, and the supernatant is taken as water for mixing the fluidized solidified soil; (4) Mix the extra fine sand, fine sand and medium sand, and stir at a rate of 120-150 r / min for 2-3 min to obtain a uniform mixture I; (5) mixing the modified graphite tailings, red mud, slag, fly ash and steel slag, and stirring at a rate of 120-150 r / min for 2-3 min to obtain a uniform mixture II; (6) mixing the defoamer with part of the water, stirring at a rate of 200-300 r / min for 1-2 min, to obtain an additive solution I; mixing the water reducer with part of the water, stirring at a rate of 200-300 r / min for 1-2 min, to obtain an additive solution II; mixing the composite thickener with part of the water, stirring at a rate of 200-300 r / min for 1-2 min, to obtain an additive solution III; mixing the foaming agent with part of the water, stirring at a rate of 200-300 r / min for 1-2 min, to obtain an additive solution IV; (7) Add water to half of the mixture, mix mixture I and mixture II, stir at a rate of 120-150 r / min for 1-2 min, and then stir at a rate of 200-300 r / min for 2-3 min to obtain a uniform slurry I; (8) adding a composite alkali activator to slurry I, stirring at a rate of 120-150 r / min for 2-3 min, to obtain slurry II; (9) Add coarse sand, extra coarse sand and the remaining mixing water to slurry II, stir at a rate of 120-150 r / min for 1-2 min, and then stir at a rate of 200-300 r / min for 2-3 min to obtain a uniform slurry III; (10) Adding additive solution I, additive solution II, additive solution III and additive solution IV to slurry III, stirring at a rate of 200-300 r / min for 2-3 min to obtain a uniform slurry IV; (11) Add active magnesium oxide to the uniform slurry IV and stir at a rate of 200-300 r / min for 2-3 min to obtain fluidized solidified soil with synergistic effects of solid waste and slag and optimized particle size.

2. The method for preparing solid waste-slag synergistic and full-particle-size optimized fluidized solidified soil according to claim 1, characterized in that: In step (1), the shield slag obtained after dehydration treatment is graded and screened, wherein the first-level vibrating screen selected in the first-level screening treatment is a 2-mesh screen, the second-level vibrating screen selected in the second-level screening treatment is a 4-mesh screen, the third-level vibrating screen selected in the third-level screening treatment is a 10-mesh screen, the fourth-level vibrating screen selected in the fourth-level screening treatment is an 18-mesh screen, the fifth-level vibrating screen selected in the fifth-level screening treatment is a 40-mesh screen, the sixth-level vibrating screen selected in the sixth-level screening treatment is an 80-mesh screen, the seventh-level vibrating screen selected in the seventh-level screening treatment is a 200-mesh screen, and the eighth-level vibrating screen selected in the eighth-level screening treatment is a 400-mesh screen.

3. The method for preparing solid waste-slag synergistic and full-particle-size optimized fluidized solidified soil according to claim 1, characterized in that: The shield wastewater is the muddy wastewater obtained after dehydration treatment in step (1), and the mud content is less than 15% and the organic matter content is less than 5%.

4. The method for preparing solid waste-slag synergistic and full-particle-size optimized fluidized solidified soil according to claim 1, characterized in that: The foaming agent is prepared by diluting a rosin-type plant foaming agent with water at a ratio of 1:50 and then foaming the foaming agent, and the density is 45-60 kg / m 3 .

5. The method for preparing solid waste-slag synergistic and full-particle-size optimized fluidized solidified soil according to claim 1, characterized in that: The purity of the sodium sulfate is ≥99.5%, the purity of the sodium carbonate is ≥99.0%, the purity of the sodium bicarbonate is ≥99.5%, the purity of the methyldiethanolamine is ≥95.0%, the purity of the diisopropanolamine is ≥99.0%, the purity of the tetraethanolamine is ≥99.5%, and the purity of the sodium dodecyl sulfate is ≥99.5%.

6. The method for preparing solid waste-slag synergistic and full-particle-size optimized fluidized solidified soil according to claim 1, characterized in that: The composite base activator is prepared by the following steps: (1) Sodium sulfate, sodium carbonate, sodium bicarbonate and deionized water are stirred at a rate of 120-150 r / min for 2-3 min, the resulting mixture is passed through a 400-mesh sieve, and the sieved slurry is collected to obtain an inorganic base activator; (2) heating the inorganic alkali solution to 35-45° C., then adding methyldiethanolamine, diisopropanolamine and tetraethanolamine thereto at the same time and stirring to mix, and stirring at a rate of 200-300 r / min for 3-5 min; (3) adding sodium dodecyl sulfate to the solution obtained in step (2) and stirring the mixture at a rate of 300-500 r / min for 2-3 min to obtain a composite alkali activator.

7. The method for preparing solid waste-slag synergistic and full-particle-size optimized fluidized solidified soil according to claim 1, characterized in that: The composite thickener is prepared by the following steps: (1) Heat to dissolve: heat deionized water to 60-80° C., then slowly add cellulose ether into the water and stir at a rate of 200-300 r / min for 4-6 min; (2) adding starch ether, lowering the temperature to 40-60° C., gradually adding starch ether to the mixture obtained in step (1), and stirring at a rate of 200-300 r / min for 3-5 min; (3) adding bentonite, gradually adding bentonite to the mixture obtained in step (2), stirring at a rate of 600-900 r / min for 7-10 min, and controlling the temperature at 40-60° C.; (4) filtering and removing bubbles, filtering the mixture obtained in step (3) through a membrane filter to remove bubbles and impurities therein, wherein the pore size of the filter is in the range of 0.2-5 μm; (5) Adjusting the pH value: adding sodium hydroxide solution to the mixture obtained in step (4) to adjust the pH value to 7-9, thereby obtaining a composite thickener.

8. The method for preparing solid waste-slag synergistic and full-particle-size optimized fluidized solidified soil according to claim 1, characterized in that: The red mud meets the requirements of national standard GB50986-2014 before grinding; the slag meets the requirements of national standard GB / T18046-2008 before grinding, which is grade S95 slag; the fly ash meets the requirements of national standard GB / T1596-2017 before grinding, which is grade II fly ash; the steel slag meets the requirements of national standard GB / T20491-2017 before grinding; the cationic polyacrylamide meets the requirements of national standard GB / T 31246-2014; the polyaluminium chloride meets the requirements of national standard GB / T22627-2022; the cellulose ether is hydroxypropyl methylcellulose meeting national standard GB / T34263-2017, with a viscosity of 100,000 mP·S and a 300-mesh square hole sieve residue of 18%; the starch ether is carboxymethyl starch meeting national standard GB / T20375-2006, with a viscosity of 10,000 m SP, the fineness of the residue on the 300-mesh square hole sieve is 17%; the bentonite is sodium-based bentonite that complies with the national standard GB / T20973-2020, with a 2h water absorption rate of ≤150%, and the fineness of the residue on the 300-mesh square hole sieve is 6.5%; the water reducer is a polycarboxylic acid-based high-performance water reducer that complies with the provisions of the national standard GB8076-2008; the defoamer is a silicone defoamer that complies with the national standard GB / T26527-2011; the foaming agent is a rosin-type plant foaming agent that complies with the national standard GB / T35140-2017; the magnesium oxide content in the active magnesium oxide is 95%, and the density is 3.85g / cm 3 , white powder, in compliance with the provisions of standard HG / T3928-2007; the sodium bicarbonate is industrial grade sodium bicarbonate in compliance with the national standard GB / T1606-2008; the sodium sulfate is industrial anhydrous sodium sulfate in compliance with the national standard GB / T 6009-2014; the deionized water is grade III pure water in compliance with the national standard GB 6682-2012; sodium dodecyl sulfate complies with the provisions of the national standard GB / T 15963-2022.

Citation Information

Patent Citations

  • Residue soil improver for waterless gravel backfilled stratum shield driving construction

    CN105885867A

  • Alkali-activated all-solid waste seawater sea sand coral concrete for island reef and preparation process thereof

    CN116217193A